Microplate alamarblue assay for paracoccidioides susceptibility testing - de Paula e Silva, A. C. A. [UNESP]; Oliveira, H. C. [UNESP]; Silva, J. F. [UNESP]; Sangalli-Leite, F. [UNESP]; Scorzoni, L. [UNESP]; Fusco-Almeida, A. M. [UNESP]; Mendes-Giannini, Maria José Soares [UNESP] (American Society for Microbiology, 2013)
CLSI method M27-A3 is not available for use with dimorphic fungi, such as those of the Paracoccidioides genus. In this study, we developed a microdilution method and added the alamarBlue reagent to test the responses of Paracoccidioides brasiliensis and Paracoccidioides lutzii against amphotericin B and itraconazole antifungals. The test proved to be sensitive, practical, and inexpensive and can be used to monitor the activity of low-growth microorganisms and their response to various drugs. © 2013, American Society for Microbiology.
Keywords: alamarBlue; amphotericin B; itraconazole; reagent; unclassified drug; antifungal activity; antifungal susceptibility; broth dilution; controlled study; fungal strain; human; intermethod comparison; minimum inhibitory concentration; nonhuman; Paracoccidioides; Paracoccidioides brasiliensis; Paracoccidioides lutzii; priority journal; Amphotericin B; Antifungal Agents; Humans; Itraconazole; Microbial Sensitivity Tests; Oxazines; Staining and Labeling; Xanthenes